Sustainable development: economic growth engine of the producers of sandia del ejido ricardo flores magón, municipality of Tonalá, Chiapas - Pérez Pérez, Isabel; Orozco Gutiérrez, Mario; Flores Preciado, Juan; Marroquín de Aquino, Briseida (Universidad Francisco de Paula Santander, 2016)
This study was carried out in the Ejido Ricardo Flores Magón, Municipality of Tonalá, Chiapas (Mexico). It is based on the qualitative appreciations of the production process carried out by the producers of Watermelon to know the perspectives they have regarding the planting, harvesting, marketing and sale of their product, obtaining income that allows them to improve their standard of living detonating the sustainable. For this, a questionnaire was applied to 41 producers of this Ejido that represents 100% of the total producers in the community. The result that was obtained was that the watermelon planting if it represents a source of income for them and their families, however, would improve if a Control Plan for planting volumes in high seasons was implemented by the Agricultural Authorities because the Excess supply negatively impacts local market prices leading to a decrease in them.